AUDIOVISUAL METHOD IN CHILD LITERARY APPRECIATION LEARNING FOR CHARACTER BUILDING BASED ON LOCAL WISDOM OF KEMBARAN TRIBE IN WEST PAPUA - Adolina Velomena Lefaan (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2018)
The reality of modern development in education which is wide opened, does not only have positive effects but also negative effects to the mindset of schoolchildren, and in turns, it changes their characteristics too. The cultural environment in the family has also started to be influenced by many kinds of development through the social media.  It is an indication that the modern life has made the parents worried about their children’s characters.  The phenomenon can be seen from the news headlines about the life of the learners from preschoolers until the college students. This writing is aimed at implementing audiovisual method in the learning of child literature by utilizing folktales (child stories) based on the local wisdom of Kembaran tribe in West Papua, as a medium for character building in order to develop the awareness to love the environment and to have a sense of belonging to the environment as a form of a real life. By using ethnographic approach, it was found that the child literature of Kembaran tribe can build the character of the children, can establish the sociocultural values along with the awareness to keep up the spirit and to preserve the local wisdom in West Papua.